Identification and analysis of the currently available high-confidence three-dimensional activity cliffs. Issue 54 (13th June 2015) - Furtmann, Norbert; Hu, Ye; Gütschow, Michael; Bajorath, Jürgen
<x xml:space="preserve">Abstract</x> Shown is an exemplary 3D-cliff formed by two crystallographic ligands with highly similar binding modes and a significant difference in potency. The site of a major interaction difference between these compounds is encircled.